# Combine like terms. A)2y-8y+9-12^2-8y+3 B)4(2-x)-3(-5-12x)

### 1 Answer | Add Yours

Combine like terms: like terms have the same variables to the same power,

(a) `2y-8y+9-12^2-8y+3`

==> 2y-8y+9-144-8y+3 Since addition is commutative we can write

==> 2y-8y-8y+9+3-144

==> 2y-8y-8y-132 Now factor a common y out of the first 3 terms

==>y(2-8-8)-132

==>**-14y-132**

(b) 4(2-x)-3(-5-12x) Use the distributive property to lose ():

==>8-4x+15+36x rewrite using teh commutative property

==>-4x+36x+8+15 factor a common x out of the first 2 terms

==>x(-4+36)+23

==>**32x+23**